(untitled) (Teacher’s World: Journal of Education and Research, 2024)
The study focused on enhancing Standard Bangla Language (SBLA) acquisition of the students at the primary level through school-home partnership (SHP). The study was qualitative in nature. The data were collected from ten respondents, and the respondents were selected purposively. An interview schedule was developed as the data collection tool for the study. The data were analyzed by a thematic approach. The study revealed that School-Home partnership has become an important phenomenon in students’ standard Bangla language achievements. The study found it as an important measure and established a relationship between School and Home with respect to students’ SBLA. The study figured out several initiatives for enhancing SBLA through SHP. The study recommended that schools and home have to ensure a natural Standard Bangla Language (SBL) practicing environment, from where the students would acquire it. Teacher’s World: Journal of Education and Research, 49 (2),125-134